2018
DOI: 10.1021/acs.macromol.8b02087
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Forms and Microphase Structures of Poly(vinylidene fluoride-co-hexafluoropropylene) Physically and Chemically Incorporated with Ionic Liquids

Abstract: The effects of incorporating two imidazolium-type ionic liquids (ILs), 1-vinyl-3-butyl­imidazolium bis­(trifluoro­methylsulfonyl)­imide (IL-TFSI) and 1-vinyl-3-butyl­imidazolium chloride (IL-Cl), on the crystal forms and phase microstructures of poly­(vinylidene fluoride-co-hexafluoro­propylene), P­(VDF-co-HFP), were investigated. No change in the crystal form was observed with the incorporation of IL-TFSI because of the selective interaction between the IL and HFP moieties of the P­(VDF-co-HFP) molecular chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In the XRD pattern of Figure 3d, typical peaks for the pure PVDF-HFP at 2θ = 17.7, 18.4, 19.9, and 26.6°correspond to the (100), (020), (110), and (021) planes of the α phase PVDF crystals, and the intensity of the peak at 2θ = 20.4°is assigned to the β phase PVDF crystals. 42,43 The XRD patterns of SN1 and DN ionogels still display α and β phase PVDF crystals, but the intensity of scattering peaks was significantly reduced, which should be ascribed to the diluted concentration and the decrease of the crystallinity of PVDF in DN ionogels. In the FTIR spectra (Figure 3e), the bands at 491 cm −1 (δ CF 2 ), 533 cm −1 (δ CF 2 ), 614 cm −1 (δ CF 2 + δ skeleton ), 761 cm −1 (δ CF 2 + δ skeleton ), and 797 cm −1 (ρ CH 2 ) are assigned to the α phase of PVDF-HFP, the band at 840 cm −1 (ρ CH 2 ) assigned to the β phase of PVDF-HFP, and the band at 875 cm −1 (ρ CH 2 ) assigned to the amorphous phase of PVDF-HFP.…”
Section: Morphology and Internalmentioning
confidence: 98%
“…In the XRD pattern of Figure 3d, typical peaks for the pure PVDF-HFP at 2θ = 17.7, 18.4, 19.9, and 26.6°correspond to the (100), (020), (110), and (021) planes of the α phase PVDF crystals, and the intensity of the peak at 2θ = 20.4°is assigned to the β phase PVDF crystals. 42,43 The XRD patterns of SN1 and DN ionogels still display α and β phase PVDF crystals, but the intensity of scattering peaks was significantly reduced, which should be ascribed to the diluted concentration and the decrease of the crystallinity of PVDF in DN ionogels. In the FTIR spectra (Figure 3e), the bands at 491 cm −1 (δ CF 2 ), 533 cm −1 (δ CF 2 ), 614 cm −1 (δ CF 2 + δ skeleton ), 761 cm −1 (δ CF 2 + δ skeleton ), and 797 cm −1 (ρ CH 2 ) are assigned to the α phase of PVDF-HFP, the band at 840 cm −1 (ρ CH 2 ) assigned to the β phase of PVDF-HFP, and the band at 875 cm −1 (ρ CH 2 ) assigned to the amorphous phase of PVDF-HFP.…”
Section: Morphology and Internalmentioning
confidence: 98%
“…66 In the presence of ions, the resulting strong interaction between ions and the C−F bond may change the position of the bending vibration band for CH 2 −CF 2 . 38,40,67 From Figure 2c, it was seen that the vibrational bands of PVDF−CTAB appeared at the same wave number of 870 cm −1 as those of neat PVDF, showing the negligible electrostatic interaction between PVDF and CTAB ions. The negligible effect of CTAB ions is consistent with the above observation of the unchanged cooling crystallization temperature (Figure 1) and still pure αphase (Figure 2a,b) in PVDF−CTAB.…”
Section: Methodsmentioning
confidence: 95%
“…Liang et al investigated the correlation between the ion type and the crystallization polymorphism and found that the positively charged ion can effectively promote the formation of polar phases from the PVDF melt, but the negatively charged ion cannot. Thus, it has been recognized that the polar phases of PVDF could be obtained by adding the effective ions into PVDF, due to the electrostatic interaction between ions and dipoles. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as a green solvent, it can be an efficient plasticizer by inducing a reduction of the glass transition temperature of the polymer. The ionic liquids grafting onto the polymers also have been recently extensively reported, discussing the effects of ionic liquids on the polymer crystal morphology and antibacterial and antistatic properties. In our previous work, the imidazolium-based IL, [BMIm]­[BF 4 ], was used to modify the CNC suspension by simple physical mixing, resulting in the improved thermal stability and dispersion of CNC in poly­(lactic acids) matrix. However, the ILs attached to the CNC via the electrostatic interaction tend to leak and are easily washed off in subsequent processing.…”
Section: Introductionmentioning
confidence: 99%